Manual of Clinical and Practical Medicine - Sainani, G. S. (Jaypee Brothers Medical Publishers, 2018)
This manual focuses on clinical and practical medicine. Bedside examination is the most important component of practicals. Based on interpretation/ conclusions of the clinical examination, one can plan cost-effective and rational investigations to arrive at proper diagnosis and then institute the appropriate therapy. The skills needed for a competent clinical examination can only be mastered at bedside by clinical practice. This book consists of 17 chapters following as nutrition including obesity, infectious diseases, history taking and general examination, gastrointestinal system, cardiovascular system, respiratory system, nervous system, nephrology and acid base disorders, endocrine and metabolic diseases including diabetes mellitus, hematology and oncology, musculoskeletal system, electrocardiography, imaging, procedures, diet, table viva voce, and emergencies. This manual explains and stresses these points with the help of sketch diagrams. The manual offers a quick revision of clinical methods. The manual sequentially covers clinical methods, clinical cases, investigations, diagnosis and therapy principles in a concise form.